FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS MENGGUNAKAN SURVIVAL ANALYSIS - Aulia Kania Putri; Farida Titik Kristanti (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2020)
The aim of this research is to find that liquidity ratio, sales growth, audit committee, institutional ownership, managerial owership, firm size, board of director and independent commissioner can predict the possibility of financial distress. The object of the research conducted on the mining sector and basic industry and chemicals sectors listed in Indonesian Stock Exchange (IDX) 2009-2018 with a total 70 samples. This study uses survival analysis as a method with cox proportion hazard model. This result of this research that liquidity ratio and audit committee have a negative impact on financial dsitress. Meanwhile, sales growth, firm size, institutional ownership, independent commissioner, board of director and  managerial ownership does not have impact on financial distress. The implication of this study is that the company is expected to be able to maintain liquidity at a safe level and increase the internal control.